Evaluation of a Risk-Stratified, Heparin-Based, Obstetric Thromboprophylaxis Protocol. Issue 4 (October 2021) - Lu, Michelle Y.; Blanchard, Christina T.; Ausbeck, Elizabeth B.; Oglesby, Kacie R.; Page, Margaret R.; Lazenby, Allison J.; Cozzi, Gabriella D.; Muñoz Rogers, Rodrigo D.; Bushman, Elisa T.; Kaplan, Elle R.; Ruzic, Martha F.; Mahalingam, Mythreyi; et al.
Abstract : OBJECTIVE: To evaluate outcomes before and after implementation of a risk-stratified heparin-based obstetric thromboprophylaxis protocol. METHODS: We performed a retrospective cohort study of all patients who delivered at our tertiary care center from 2013 to 2018. Deliveries were categorized as preprotocol (2013–2015; no standardized heparin-based thromboprophylaxis) and postprotocol (2016–2018). Patients receiving outpatient anticoagulation for active venous thromboembolism (VTE) or high VTE risk were excluded. Coprimary effectiveness and safety outcomes were postpartum VTEs and wound hematomas, respectively, newly diagnosed after delivery and up to 6 weeks postpartum. Secondary outcomes were other wound or bleeding complications, including unplanned surgical procedures (eg, hysterectomies, wound explorations) and blood transfusions. Outcomes were compared between groups, and adjusted odds ratios (aORs) and 95% CIs were calculated using the preprotocol group as reference. RESULTS: Of 24, 229 deliveries, 11, 799 (49%) occurred preprotocol. Although patients were more likely to receive heparin-based prophylaxis postprotocol (15.6% vs 1.2%, P <.001), there was no difference in VTE frequency between groups (0.1% vs 0.1%, odds ratio 1.0, 95% CI 0.5–2.1). However, patients postprotocol experienced significantly more wound hematomas (0.7% vs 0.4%, aOR 2.34, 95% CI 1.54–3.57), unplanned surgical procedures (aOR 1.29, 95% CI 1.06–1.57), and blood transfusions (aOR 1.34, 95% CI 1.16–1.55). CONCLUSION: Risk-stratified heparin-based thromboprophylaxis in a general obstetric population was associated with increased wound and bleeding complications without a complementary decrease in postpartum VTE. Guidelines recommending this strategy should be reconsidered. Abstract : Risk-stratified heparin-based obstetric thromboprophylaxis was associated with increased wound and bleeding complications without decreased postpartum venous thromboembolisms.